EVALUATION OF THE CERTIFICATE OF MEDICAL PEDAGOGY OF THE FACULTY OF MEDICINE OF TLEMCEN-ALGERIA, CLASS OF 2017-2018 - A.Zouaoui; N.Berber; K.Meguenni (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
By the 2008 decree of 22 December 2014, creating a subspecialty diploma in medical pedagogy, the training in medical pedagogy in Tlemcen was thus created in 2017(1). Since then, our faculty has been able to welcome two classes: the first 2017-2018 and a second 2018-2019.A legal obligation and an integral part of the training action itself, the evaluation of the latter is part of an improvement process continue (1),(2),(3). The evaluation process must be thought out in its entirety(4), that of training in medical pedagogy at our faculty has already been initiated by Dr. Ouadah concerning the 2017-2018 promotion(5). It therefore seemed appropriate to us to ensure continuity, with the aim of drawing up an inventory of the contribution of the 2017-2018 training in medical education, after several months of its end, characterizing a cold evaluation.